Desenvolvimento de nanopartículas pH-responsivas à base de goma do cajueiro e doxorrubicina com potencial de aplicação contra o câncer - Ribeiro, Irisvan da Silva (2023)
Polymeric prodrugs obtained from polysaccharide-drug conjugation via pH-responsive covalent bonds are a promising strategy for the administration of anticancer drugs at the target site (cancer cells), due to the acidic microenvironment in tumor cells and tissues. The present work proposed the synthesis of prodrugs from cashew gum and doxorubicin via Schiff base formation reaction and amidation reaction through the carbodiimide chemistry. The synthesized prodrugs were characterized by infrared spectroscopy, hydrogen nuclear magnetic resonance, high-performance liquid chromatography and size exclusion chromatography. The efficiency of prodrug synthesis was determined by UV-vis spectroscopy. The drug conjugation efficiency was 64%, 74% and 75% for prodrugs synthesized via amine, amide and imine bond formation, respectively. The prodrugs exhibited the ability to self-organize in aqueous media with critical association concentration lower than 200 µg mL–1. Prodrug nanoparticles were obtained by direct ultrasonic method in phosphate buffer and/or distilled water and were characterized by dynamic light scattering, scanning electron microscopy and atomic force microscopy. The size distribution of the nanoparticles was unimodal, with a negative zeta potential. The hydrodynamic diameter in phosphate buffer ranged from 160 to 245 nm, and the diameter of dry nanoparticles ranged from 20 to 135 nm. The prodrug nanoparticles showed a extended and pH-dependent release profile. The nanoparticles of the prodrugs GC-S-DOX and GCCM-D-DOX exhibited cytotoxic activity against human colorectal cancer cells (HCT-116) and human breast cancer cells (MCF-7), with lower cytotoxicity than DOX against non-tumor murine fibroblast cells (L929). Furthermore, the intracellular uptake assay confirmed that GC-S-DOX (cashew gum-Schiff base-doxorubicin) prodrug nanoparticles were absorbed by HCT-116 cells.